Making An Online Catalog for the New Target Market of Kuala Batakan Cottage III Balikpapan - Stephany Mauren Tesalonika (Institute of Research and Community Outreach - Petra Christian University, 2023)
Kuala Batakan Cottage III Balikpapan is a company that sells services such as houses and furnished apartments. The problem is that sales keep decreasing during the pandemic because the main target market is gone. However, the company plans to refocus the target market, especially during the pandemic. The solution is to refocus the target market to the local people of Balikpapan. The approach of the solution is by making an online catalog which later will be shared in the Facebook Community in Balikpapan city. The online catalog which includes eye-catching photos and the description will be shared in the form of a link. The catalog was created according to the survey from the current potential customers. Therefore, by having an online catalog shared on Facebook, Kuala Batakan Cottage III Balikpapan will be able to refocus its new target market.